Frantumi di un (s)oggetto di fede (Mantichora. Italian Journal of Performance Studies, 2025)
In the second chapter of his personal trilogy on human paradise, Paradies: Glaube (2012), Austrian director Ulrich Seidl changes the object of faith from a symbol of pure transcendence to authentic immanence. Lost among the accumulations of despair, the sacred thing is attacked by the rest; still, it bears a profound meaning of which it becomes an expression. But if for Seidl man is an infinite abyss, then of what does the object become a symbol: of the inevitable destruction of man? Is this perhaps the transcendent, inconceivable, obscurely intuited meaning? And if the object does not survive, what meaning comes from its destruction?